2008
DOI: 10.1097/01.prs.0000299452.24743.65
|View full text |Cite
|
Sign up to set email alerts
|

Barbed Sutures: A Review of the Literature

Abstract: Suspension of the aging face with barbed sutures offers the promise of a minimally invasive technique with diminished adverse events. The technique is in its infancy, but it has potential to be a useful and effective clinical tool as further innovations are made in the clinic and laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
182
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(185 citation statements)
references
References 32 publications
1
182
0
2
Order By: Relevance
“…Recent publications have described their potential for surgeons and patients in fixation and tissue approximation [14]. These distinctive sutures are generally unidirectional or bidirectional.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications have described their potential for surgeons and patients in fixation and tissue approximation [14]. These distinctive sutures are generally unidirectional or bidirectional.…”
Section: Discussionmentioning
confidence: 99%
“…Various animal studies have confirmed equivalence of bio-compatibility and tensile strength of barbed sutures compared to the standard bioabsorbable sutures [9][10][11]. With availability of bioresorbable bidirectional barbed sutures (BBS), and unidirectional barbed sutures (UBS) in Plastic Surgery and Gynecological Surgery [12][13][14][15], we utilized these sutures for VUA and compared UBS with Polyglecaprone-25 suture.…”
Section: Introductionmentioning
confidence: 97%
“…24 The homogeneous tension distribution of a continuous suture, therefore, offers advantages with respect to inflammation and tissue viability. Moreover, while avoiding local ischemia, [25][26][27][28][29] the continuous suture using barbed sutures allows a comparable or even tighter wound closure overall 30,31 with seemingly comparable cosmetic results. 32 Several clinical trials have suggested a similar complication rate for wound closure with barbed sutures as that with monofilament suture material, for example, in total knee arthroplasty, 21,33 vesicourethral anastomosis, 34 and gynecologic surgery.…”
mentioning
confidence: 99%